Dissemination Strategies and Usage of Psychological Assistance Hotlines During the COVID-19 Outbreak in China - Ma, Ruofan; Nguyen, Rin; Oakman, Jonathan M. (Frontiers in Communication, 2020)
When the 2019 novel coronavirus disease (COVID-19) was rapidly spreading in China in early 2020, China’s National Health Commission quickly responded to the psychological crisis by issuing guidelines for establishing mental health intervention systems, including providing psychological assistance hotlines. However, recent critiques have emphasized China’s lack of pre-established mental health interventions which resulted in an inefficient response. This is the first empirical study to systematically examine mental health service use in China during the COVID-19 outbreak. The current study focused on the use of mental health hotlines in a Northern Chinese region. This region originally had a regional level hotline. During the outbreak, 12 out of its 16 sub-regional juridical areas started providing their own hotlines. Data regarding the regional level hotline and the 12 sub-regional level hotlines were obtained, including daily number of calls received, strategies for disseminating hotline services, and callers’ expressed concerns. Confirmed COVID-19 cases in China, in the region, and in each of the sub-regional juridical area were also recorded daily during China’s peak period of COVID-19. Analyses of these data revealed that the mental health hotlines tended to have low usage overall. Hotlines that merely provided their numbers to community centers and quarantine centers tended to receive few calls. Hotlines that encouraged individuals to advertise the service on personal social media accounts tended to receive more calls. The daily number of confirmed COVID-19 cases in the country was closely related the number of phone calls received at the regional hotline. Sub-regional hotline operators reported that a significant proportion of callers had concerns about contracting COVID-19, negative emotions from prolonged social isolation, and family conflicts while stay-at-home policies were implemented. It was also observed that the sub-regional level hotlines did not start until COVID-19 cases in the country started to decline. Overall, the psychological assistance hotlines provided during COVID-19 satisfied some mental health needs. However, consistent with recent commentaries, the hotline services were not established during the time that demand likely peaked. Future studies are warranted to determine the best strategies to improve the accessibility of mental health hotline services.